2012
DOI: 10.2134/jeq2011.0132
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and Hydrochar Effects on Greenhouse Gas (Carbon Dioxide, Nitrous Oxide, and Methane) Fluxes from Soils

Abstract: With a growing world population and global warming, we are challenged to increase food production while reducing greenhouse gas (GHG) emissions. We studied the effects of biochar (BC) and hydrochar (HC) produced via pyrolysis or hydrothermal carbonization, respectively, on GHG fluxes in three laboratory incubation studies. In the first experiment, ryegrass was grown in sandy loam mixed with equal amounts of a nitrogen-rich peanut hull BC, compost, BC+compost, double compost, or no addition (control); wetting-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
168
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(200 citation statements)
references
References 80 publications
14
168
0
6
Order By: Relevance
“…), and Easter lily (Lilium longiflorum). Biochar is considered a carbon sink for terrestrial ecosystems, and was reported to reduce greenhouse gas emission in field studies [45,46]. Therefore, introducing biochar to garden soil through transplanting plants produced with biochar and studying biochar's effects on greenhouse gas emission during and after greenhouse production would be an interesting direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…), and Easter lily (Lilium longiflorum). Biochar is considered a carbon sink for terrestrial ecosystems, and was reported to reduce greenhouse gas emission in field studies [45,46]. Therefore, introducing biochar to garden soil through transplanting plants produced with biochar and studying biochar's effects on greenhouse gas emission during and after greenhouse production would be an interesting direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Gas samples were analysed within 36 h on a gas chromatograph (Shimadzu GC-14B, Kyoto, Japan) with a flame ionization detector (O 2 , CH 4 ) and an electron capture detector (N 2 O, CO 2 ) operated at 230 and 320 °C with N 2 as carrier gas (25 ml min − 1 ) 30,36 . The length of the column (PorapakQ, Fa.…”
Section: Methodsmentioning
confidence: 99%
“…The process normally operates at pressures and temperatures of 15-25 MPa and 180-250°C, respectively (Kammann et al, 2012). The C-content of hydrochar is lower relative to BC as some biomass-C leaches as dissolved organic carbon (DOC) during the reaction with water, although both the C and N gaseous losses are almost negligible (Appendix Table 1; Kammann et al, 2012;Subedi et al, 2015).…”
Section: Pyrolysis Processing Conditionsmentioning
confidence: 99%
“…Many recent studies have reported increased crop yield (Subedi et al, 2016a;Vaccari et al, 2011;Usman et al, 2016;Kammann et al, 2012;Baronti et al, 2010;Uzoma et al, 2011;Houben et al, 2013;Genesio et al, 2015;Cornelissen et al, 2013;De La Rosa et al, 2014;Fox et al, 2014;Gregory et al, 2014;Lin et al, 2015;Schmidt et al, 2015;Butnan et al, 2015;Laghari et al, 2015;Mandal et al, 2016). Others have reported no yield effect (Cornelissen et al, 2013;Uzoma et al, 2011;Nelissen et al, 2015;Subedi et al, 2016aSubedi et al, , 2016bNielsen et al, 2014;Tammeorg et al, 2014;Suddick and Six, 2013;Schmidt et al, 2014;Bass et al, 2016).…”
Section: Biochar Effects On Crop Productivitymentioning
confidence: 99%